Rabies in Iraq: trends in human cases 2001-2010 and characterisation of animal rabies strains from Baghdad. - Daniel L Horton; Mashair Z Ismail; Eman S Siryan; Abdul Raheem A Wali; Husam E Ab-dulla; Emma Wise; Katja Voller; Graeme Harkess; Denise A Marston; Lorraine M McElhinney; Salah F Abbas; Anthony R Fooks (Public Library of Science (PLoS), 2013)
Control of rabies requires a consistent supply of dependable resources, constructive cooperation between veterinary and public health authorities, and systematic surveillance. These are challenging in any circumstances, but particularly during conflict. Here we describe available human rabies surveillance data from Iraq, results of renewed sampling for rabies in animals, and the first genetic characterisation of circulating rabies strains from Iraq. Human rabies is notifiable, with reported cases increasing since 2003, and a marked increase in Baghdad between 2009 and 2010. These changes coincide with increasing numbers of reported dog bites. There is no laboratory confirmation of disease or virus characterisation and no systematic surveillance for rabies in animals. To address these issues, brain samples were collected from domestic animals in the greater Baghdad region and tested for rabies. Three of 40 brain samples were positive using the fluorescent antibody test and hemi-nested RT-PCR for rabies virus (RABV). Bayesian phylogenetic analysis using partial nucleoprotein gene sequences derived from the samples demonstrated the viruses belong to a single virus variant and share a common ancestor with viruses from neighbouring countries, 22 (95% HPD 14-32) years ago. These include countries lying to the west, north and east of Iraq, some of which also have other virus variants circulating concurrently. These results suggest possible multiple introductions of rabies into the Middle East, and regular trans-boundary movement of disease. Although 4000 years have passed since the original description of disease consistent with rabies, animals and humans are still dying of this preventable and neglected zoonosis.